Entrepreneurship Development on Modern India - Dr. S. Chandrsekar, Dr. S. Ramachandran (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The Entrepreneurial Development is not a recent concept that has suddenly caught the attention of the government of our nation. It has been there since the Vedic age and has continued to influence the culture and economy or our country down the ages. Today it is considered to be an important tool of development, industrialization and a solution to the perennial problem of unemployment. In thepresent paper an attempt has been made to study the evolution of Entrepreneurship in India and the current scenario of entrepreneurship in the development of a nation. The data used in the study are mainly from the secondary source.